Escape to you - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Montana heat., 2017)
He discovered her during a Montana blizzard, freezing cold, impossibly vulnerable, a little boy by her side. Undercover DEA Agent Beck “Trigger” Cooke is astonished to recognize Ashley Swan<U+2014>award-winning actress, famous beauty<U+2014>and missing for over a year. To keep her and the child hidden from a sadistic madman, he secrets the pair away to his isolated home. No longer a prisoner, and protected at Hope Ranch, Ashley recovers and learns the tall, tempting federal agent may have a dark past, but it hasn<U+2019>t destroyed his sense of honor. As they shed past roles and find common ground, Ashley and Trigger can<U+2019>t help but fall slowly, carefully, in love. But danger still lurks outside the boundaries of Hope Ranch, for until her crazed captor is brought to justice, and Trigger<U+2019>s undercover past is laid to rest, none of them will ever be truly safe<U+2026>